Integration of substrate-gate couple p-type anatase TiO2 for field-effect transistor based biosensors - Adzhri Rahmat (School of Nano Electronic Engineering, Universiti Malaysia Perlis, 2017)
The objective of this project is to fabricate FET based bio-sensor with integration of substrate gate TiO2 as transducer, bridging between source and drain. The completed bio-sensors will be characterized in terms of physical, chemical and electrical. These objectives are accomplished with the following specific objectives ; to fabricate FET devices with integration of substrate-gate coupling and deposition of TiO2 between the channels by utilizing thin body SOI substrate for bio-sensing ; to characterized the architecture design and structure of the device and physical and crystallinity of the TiO2 thin film and utilized the effect of substrate-gate biasing in terms of electrical mobility of TiO2 thin film ; to functionalized the surface of TiO2 thin film for specific cTnI antibody-antigen interaction ; to test the ability of the device in term of differentiating electrical properties of each surface functionalization with the effect of different substrate-gate biasing for enhancing the device sensitivity.